Economic Contributions of the Vanilla Value Chain in the SAVA Region, Madagascar - Ralainirina Razokiny Eric; Jean Tsitaire Arrive; Ralaivao Hanginiaina Emynorane (Bisnis, Jasa dan Keuangan, 2026)
This study examines the economic contribution of the vanilla value chain in the SAVA region of Madagascar and its implications for household livelihoods and regional development. A qualitative case study approach was employed, drawing on field observations, focus group discussions, document analysis, and in-depth interviews with 30 participants representing key actors across the vanilla value chain, including smallholder farmers, collectors, cooperative representatives, exporters, and local stakeholders. The results indicate that vanilla production constitutes the primary source of cash income for most households and plays a significant role in regional economic activity. However, the benefits are unevenly distributed and accompanied by pronounced vulnerability to price volatility, environmental risks, and external shocks. Limited livelihood diversification and weak institutional support constrain the translation of short-term income gains into long-term economic security. Overall, the study shows that the economic contribution of the vanilla value chain remains highly conditional on governance structures and livelihood resilience.